Prevalence of human papillomavirus genotypes in preinvasive and invasive cervical cancer-A UKM study - Sharifa Ezat WP; Sharifah NA; Sayyidi Hamzi AR; Norin Rahayu S (Penerbit UKM, 2010)
A cross sectional study was done to determine the prevalence and distribution of human papillomavirus (HPV) genotypes in pre-invasive (cervical intraepithelial neoplasia, grade 3 or CIN 3) and invasive cervical cancer (ICC), in Universiti Kebangsaan Malaysia Medical Centre (UKMMC). A total of 80 paraffin-embedded tumour tissue blocks (20 CIN 3, 60 invasive cancers) between 1999 to 2007 were retrieved from the archives of the Department of Pathology. Patient’s medical records were obtained from the Medical Records Office. Among invasive cancers (n=60), squamous cell carcinoma (SCC) account for 75% and adenocarcinoma 25%. The mean age of cases studied was 52.0 ± 12.2 years and Chinese was the predominant ethnicity (66.3%). Twelve HPV genotypes were identified, namely, HPV 16, 33, 18, 39, 52, 45, 58, 59, 31, 35, 6 and 11. The prevalence of HPV was 92.5% with types 16 being the most common (73.8%), followed by types 33 (30%) and 18 (22.5%). A total of 31 cases (38.8%) showed single HPV genotype, while 43 (53.8%) had multiple HPV (two genotypes or more) genotypes. In ICC, HPV 16, followed by types 33, 18, 52 and 39 were the top five common HPV genotypes detected. High prevalence of HPV and multiple HPV infections were major findings among patients with pre-invasive and invasive cervical cancer